2022
DOI: 10.1590/1809-4392202100372
|View full text |Cite
|
Sign up to set email alerts
|

Behind the forest restoration scene: a socio-economic, technical-scientific and political snapshot in Amazonas, Brazil

Abstract: Conservation of the Amazon rainforest is a global concern and is supported by the Brazilian government’s ratification of the Bonn Challenge and Paris Agreement and the introduction of national regulations on vegetation protection and restoration. Amazonas is the largest and least deforested of the states occupied by the Brazilian Amazon (< 3%). We carried out a survey on the current state and growth potential of seed and seedling production in Amazonas state, pointing out constraints where future investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The main bottlenecks pointed out in seedling production were low profitability, high production costs, and the difficulty of selling seedlings. Marques et al (2022) also observed annual production of all nurseries below maximum capacity in Amazonas state. The authors estimated the native seedlings production of 1,258,600 seedlings in 2018, which could be increased by up to seven times (9.7 million seedlings year -1 ).…”
Section: Productive Capacitymentioning
confidence: 63%
See 2 more Smart Citations
“…The main bottlenecks pointed out in seedling production were low profitability, high production costs, and the difficulty of selling seedlings. Marques et al (2022) also observed annual production of all nurseries below maximum capacity in Amazonas state. The authors estimated the native seedlings production of 1,258,600 seedlings in 2018, which could be increased by up to seven times (9.7 million seedlings year -1 ).…”
Section: Productive Capacitymentioning
confidence: 63%
“…The authors suggest that this is related to low demand for native species, which is caused by socioeconomic, technical-scientific and political bottlenecks. The predominance of nurseries (60%) with small-scale production (<50,000 seedlings per year) in RJ (Figure 2) and in Amazonas states (Marques et al, 2022) contrast what was observed in São Paulo, where large (> 500,000 seedlings) and medium-large nurseries are the majority (100,000 to 499,000 seedlings.year-1) across all categories from public to private nurseries .…”
Section: Productive Capacitymentioning
confidence: 77%
See 1 more Smart Citation